Two new species of Microterys Thomson, 1876 (Hymenoptera: Encyrtidae) from Tibet, China - Li, Hong-Liang; Zhang, Yan-Zhou (Zootaxa, 2021)
Two new species of Microterys (Hymenoptera: Encyrtidae), Microterys motuoensis Li & Zhang sp. nov. and Microterys tibetensis Li & Zhang sp. nov., are described from Tibet, China. Microterys motuoensis was reared from Kermes sp. (Hemiptera: Kermesidae) on Castanea sp. (Fagales: Fagaceae), and Microterys tibetensis from Saissetia sp. (Hemiptera: Coccidae) on Tetracera sarmentosa Vahl. (Dilleniales: Dilleniaceae).